If g(x)=4x^2-3x^2+2x-2, find g(2) and g(1/2)?

Attachment image

1 Answer

Relevance
  • Philip
    Lv 6
    4 months ago

    You've written g(x) = 4x^2-3x^2+2x-2. I'm uncertain about your 1st term 4x^2.

    If you really meant 4x^2 then g(x)=x^2+2x-2=(x+1)^2-3, g(2)=6, g(1/2) =-(3/4). 

    If you originally wanted 4x^3 as the 1st term, then g(x) = 4x^3-3x^2+2x-2, g(2)

    = 4*8 -3*9 +2*3 -2 = 32-27+6-2 = 38-29 = 9 and g(1/2) = 4/8 -3/4 + 2 = (7/4).

Still have questions? Get answers by asking now.